2011
DOI: 10.1007/s13311-010-0006-0
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in Psychiatric Disorders

Abstract: Summary In psychiatry, neuroimaging facilitates the diagnosis of psychiatric disorders and the development of new medications. It is used to detect structural lesions causing psychosis and to differentiate depression from neurodegenerative disorders or brain tumors. Functional neuroimaging, mostly in the form of molecular neuroimaging with positron emission tomography or single photon emission tomography, facilitates the identification of therapeutic targets, the determination of the dose of a new drug needed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 57 publications
0
28
0
Order By: Relevance
“…These included the subgenual anterior cingulate cortex activity that correlated with depression [34][36] and dorsal midbrain and anterior temporal lobe activity correlating with anxiety [37][39]. There are no resting state FDG PET studies in anxiety disorders that have shown abnormalities in baseline metabolic activity in the entorhinal cortex or amygdala but amygdala activity is inducible in many anxiety subtypes when measured with fMRI [40], [41]. Baseline glucose metabolism has been found to be higher in the left amygdala in depressed patients when analysis is limited to a region of interest over the amygdala [42].…”
Section: Discussionmentioning
confidence: 99%
“…These included the subgenual anterior cingulate cortex activity that correlated with depression [34][36] and dorsal midbrain and anterior temporal lobe activity correlating with anxiety [37][39]. There are no resting state FDG PET studies in anxiety disorders that have shown abnormalities in baseline metabolic activity in the entorhinal cortex or amygdala but amygdala activity is inducible in many anxiety subtypes when measured with fMRI [40], [41]. Baseline glucose metabolism has been found to be higher in the left amygdala in depressed patients when analysis is limited to a region of interest over the amygdala [42].…”
Section: Discussionmentioning
confidence: 99%
“…Functional brain scans, such as SPECT (single photon emission computed tomography) or PET (positron emission tomography) have shown that patients presenting with the same symptoms of depression can have very different functional features occurring in their brains (24). Indeed, some of the anatomic circuits of depression and mood regulation have been revealed by converging evidence from SPECT, PET, and fMRI studies of depression, as well as the analysis of the effects of either traumatic lesions resulting in depressive symptoms or surgical interventions used to treat severe cases of depression (25,26). A network of brain regions have been revealed by convergent neuroimaging findings, which includes the dorsal prefrontal cortex, ventral prefrontal cortex, anterior cingulate gyrus, amygdala, hippocampus, striatum, and thalamus, and together contribute to the pathophysiology of depression (27)(28)(29).…”
Section: Brain Function and Psychiatry In Historymentioning
confidence: 99%
“…This misalignment between etiologies and diagnoses is problematic. To improve the diagnosis and treatment of primary psychiatric disorders, efforts have been made to search for reliable biomarkers that would help elucidate the neurobiological mechanisms of psychiatric disorders, identify at‐risk populations, develop pharmaceutical drugs, and provide etiology‐based treatments …”
Section: Introductionmentioning
confidence: 99%
“…To improve the diagnosis and treatment of primary psychiatric disorders, efforts have been made to search for reliable biomarkers that would help elucidate the neurobiological mechanisms of psychiatric disorders, identify at-risk populations, develop pharmaceutical drugs, and provide etiology-based treatments. 5 In 1976, the newly invented computer tomography (CT) was used to study enlarged cerebral ventricles in schizophrenic patients, providing hope that neuroimaging would be an effective tool to identify reliable biomarkers for psychiatry. 4,6 In the following decades, research interest and output in this field have grown exponentially, made possible by rapid emergence of new and improved neuroimaging modalities, particularly the positron emission tomography (PET, first use in psychiatry in 1979 7 ), structural (sMRI, first use in psychiatry in 1983 8 ), and functional magnetic resonance imaging (fMRI, first use in psychiatry in 1994 9 ).…”
Section: Introductionmentioning
confidence: 99%